One hundred hungry ants - Pinczes, Elinor J.; MacKain, Bonnie (Boston : Houghton Mifflin, 1993)
One hundred hungry ants head towards a picnic to get yummies for their tummies, but stops to change their line formation, showing different divisions of one hundred, cause them to lose both time and food in the end.
Keywords: Ants -- Fiction; Division -- Fiction; Stories in rhyme